Variants in CUL4B are Associated with Cerebral Malformations. Issue 1 (January 2015) - Vulto‐van Silfhout, Anneke T.; Nakagawa, Tadashi; Bahi‐Buisson, Nadia; Haas, Stefan A.; Hu, Hao; Bienek, Melanie; Vissers, Lisenka E.L.M.; Gilissen, Christian; Tzschach, Andreas; Busche, Andreas; Müsebeck, Jörg; Rump, Patrick; et al.
<x xml:space="preserve">Abstract</x> This study reports 25 patients from eleven families with variants in CUL4B, known to cause X‐linked intellectual disability. Nine different novel variants were identified and pathogenicity of all non‐truncating variants was confirmed. Neuroimaging data, available for 15 patients showed the presence of cerebral malformations comprising malformations of cortical development, ventriculomegaly and diminished white matter volume in ten patients. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>